Performance Evaluation of Highest Degree Clustering Algorithm in Mobile ad-hoc Networks - Haitham Shiaibth Chasib, Alyaa Abdulmunem M. Al-Najjar (International Journal of Advanced Science and Technology, 2020)
A Mobile Ad hoc Network (MANET) is a self-sorted out and dynamic multi-hop wireless network involved of mobile nodes that communicate with one another with no fixed infrastructure. In our work, we clarified the mechanism for selecting the cluster head of (HD) algorithm, created a virtual work environment, and changed the values of some parameters of the work environment. Also, studied the effect of those parameters on the performance of the algorithm in terms of raising the performance of the algorithm or in terms of making its performance worse as possible. The first scenario describes the factors that raise the performance of the algorithm. while the second one shows the factors that affect the performance of the algorithm, which is worse and the instability of the results of some of the criteria that we used to measure the level of work on the network.